Toward a Sociotechnical Framework for Misinformation Policy Analysis - Zhu, Xiaohua; Yang, Shengnan (The Usage and Impact of ICTs During the Covid-19 Pandemic, 2023)
The challenge of widespread misinformation has expanded during the COVID-19 pandemic. Governments worldwide have adopted or are designing a variety of information policies and tools to cope with the exacerbated challenge of misinformation. To understand the complexity and nuanced realities of government misinformation regulatory practices, we developed an analytical framework, drawing from policy design studies and the social informatics perspectives, which emphasize two aspects of misinformation policies. First, we identified agents, actions, and target groups as the essential components of policy design. We then incorporated three sociotechnical dimensions related to misinformation regulation-the context from which misinformation policies originate; the specific issues, topics, and forms of misinformation; and the channels for its creation and spread. We applied this framework to 139 policy documents systematically collected from the federal government of the United States and the central government of China, for the purpose of understanding and comparing misinformation regulations in two distinct contexts. Beyond those well-known political narratives in each country, this chapter identified the nuanced differences in their misinformation policies and the different stages or maturity of misinformation policymaking. The empirical findings showcase the analytical power of this framework and shed light on policy practices and the direction of future research.